Virtual Reality and Sound Intervention under Chemotherapy (ViSu): study protocol for a three-arm randomised-controlled trial - Andre Karger; Luisa Ernsten; Steffen Holsteg; Nora K Schaal; Luisa M Keßling; Nele Schmutzler; Tanja N Fehm; Verena Friebe; Norbert Gattermann; Eugen Ruckhäberle (BMJ Open)
Introduction Patients undergoing chemotherapy often experience side effects during treatment, including psychological distress and symptoms of anxiety and depression. Interventions during chemotherapy that divert attention from potentially aversive environmental factors have been demonstrated to have a beneficial impact on these symptoms. Virtual reality (VR) offers the potential to visually and audibly disengage from the surrounding environment and can create an alternative sense of presence. This could facilitate the implementation of active guided interventions that may prove more effective than receptive interventions, such as listening to music. The present study examines the feasibility, acceptance and effectiveness of a VR intervention and a music intervention during chemotherapy.Methods The single-centre three-arm, randomised-controlled trial investigates the efficacy of a VR mindfulness intervention and a music intervention in patients with cancer undergoing chemotherapy at the University Hospital Düsseldorf, Germany. Patients were randomly assigned to receive either (a) the VR mindfulness intervention, (b) the receptive music intervention or (c) the standard care (control group) in two consecutive chemotherapy sessions. A comprehensive psychological assessment and self-ratings using visual analogue scales will be conducted with situational anxiety as the primary outcome measure. Additionally, secondary measures will be employed to assess cancer-related anxiety, self-efficacy and chemotherapy-related side effects. Furthermore, salivary cortisol, heart rate and blood pressure will be recorded. At the end of the study, an evaluation questionnaire will be completed. It is planned to enrol 82 patients.Ethics and dissemination The study has been approved by the ethics committee of the medical faculty of the Heinrich-Heine-University Düsseldorf (2022-1880). Written informed consent is obtained from the patients prior to participation. The results will be published in international scientific, peer-reviewed journals. Conference presentations are also planned.Trial registration number German Clinical Trials Register (DRKS00029738).